1979
DOI: 10.1111/j.2042-7158.1979.tb13437.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of cryobiology to the microbiological assay of nystatin

Abstract: Improvements in the reproducibility of nystatin agar diffusion assays have been achieved by the use of liquid nitrogen stored inocula and deep frozen standard stock solutions. The overall percentage variability of the assay has been reduced from over 5% with daily prepared standards and inocula to around 1 % with a frozen inocula and to 0.6% with a combination of frozen inocula and standards. The implications of these improvements in the standardization of nystatin assays, and microbiological assays generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Flow microcalorimetry has proved to be an excellent tool for studying the efficacy of drugs in combination. Cosgrove et al [63] was one of the first to publish work in this field. The study showed that clotrimazole reduced the effectiveness of amphotericin B against Saccharmoyces crevisiae Fig.…”
Section: Drug Combinations Synergic / Antagon-istic Effectsmentioning
confidence: 98%
“…Flow microcalorimetry has proved to be an excellent tool for studying the efficacy of drugs in combination. Cosgrove et al [63] was one of the first to publish work in this field. The study showed that clotrimazole reduced the effectiveness of amphotericin B against Saccharmoyces crevisiae Fig.…”
Section: Drug Combinations Synergic / Antagon-istic Effectsmentioning
confidence: 98%